Antibacterial and Biocompatible Titanium‐Copper Oxide Coating May Be a Potential Strategy to Reduce Periprosthetic Infection: An In Vitro Study. Issue 3 (March 2017) - Norambuena, German A.; Patel, Robin; Karau, Melissa; Wyles, Cody C.; Jannetto, Paul J.; Bennet, Kevin E.; Hanssen, Arlen D.; Sierra, Rafael J.
Abstract: Background: Periprosthetic infections are devastating for patients and more efficacious preventive strategies are needed. Surface‐modified implants using antibacterial coatings represent an option to cope with this problem; however, manufacturing limitations and cytotoxicity have curbed clinical translation. Among metals with antibacterial properties, copper has shown superior in vitro antibacterial performance while maintaining an acceptable cytotoxicity profile. A thin film containing copper could prevent early biofilm formation to limit periprosthetic infections. This pilot study presents the in vitro antibacterial effect, cytotoxicity, and copper ion elution pattern of a thin film of titanium‐copper oxide (TiCuO). Questions/purposes: (1) Do titanium alloy (Ti6Al4V) discs coated with a thin film of TiCuO reduce Staphylococcus epidermidis biofilm and planktonic cell density compared with uncoated discs? (2) Do Ti6Al4V discs coated with a thin film of TiCuO affect normal human osteoblast viability compared with untreated cells? (3) Is copper ion concentration generated by coated discs lower than previously published copper ion concentrations that cause 50% toxicity in similar human cell lines in vitro (TC50)? Methods: Ninety Ti6Al4V discs (12.5 mm diameter; 1.25 mm thick) were used in this study. Seventy‐two Ti6Al4V discs were coated with a thin film of either titanium oxide (TiO) or TiCuO containing 20%, 40%, or 80% copper using high‐power impulse magnetron sputtering (HiPIMS). Eighteen Ti6Al4V discs remained uncoated for control purposes. We tested antibacterial properties of S epidermidis grown on discs in wells containing growth medium. After 24 hours, planktonic bacteria as well as biofilms removed by sonication were quantitatively cultured. Annexin/Pi staining was used to quantify in vitro normal human osteoblast cell viability at 24 hours and Day 7, respectively. Copper elution was measured at Days 1, 2, 3, 7, 14, and 28 using an inductively coupled plasma mass spectrometer to analyze aliquots of culture medium. Copper ion concentration achieved at 24 hours was compared with previously published TC50 for gingival fibroblast, a phenotypically similar cell line with available data regarding copper ion exposure. Results: Discs coated with TiCuO 80% copper showed greater biofilm and planktonic cell density reduction when compared with other tested compositions (analysis of variance [ANOVA]; p < 0.001). Discs coated with TiCuO 80% copper showed mean biofilm and planktonic cell density of 4.0 log10 (SD = 0.4) and 5.7 log10 (SD = 0.2). Discs coated with TiCuO 80% showed a mean difference in biofilm and planktonic cell density of 2.5 log10 (95% confidence interval [CI], 1.9‐3.1 log10; p < 0.001) and 1.2 (95% CI, 0.6‐1.8; p < 0.001), respectively, when compared with uncoated discs. Normal human osteoblast viability did not differ among all groups at 24 hours (ANOVA; p = 0.2) and Day 7 (ANOVA; p = 0.7). Discs coated with TiCuO 80% copper showed a mean difference (95% CI) in relative cell viability (%) at 24 hours and Day 7 of 31.1 (95% CI, −19.4 to 81.7; p = 0.4) and −5.0 (95% CI, −7.8 to 17.9; p = 0.9), respectively, when compared with untreated cells. For all TiCuO‐coated discs, copper ion elution peaked at 24 hours and slowly decreased in a curvilinear fashion to nearly undetectable levels by Day 28. Discs coated with TiCuO 80% copper showed mean copper ion concentration at 24 hours of 269.4 μmol/L (SD = 25.2 μmol/L) and this concentration was lower than previously published TC50 for similar human cell lines at 24 hours (344 μmol/L, SEM = 44 μmol/L). Conclusions: This pilot study demonstrates a proof of concept that a thin‐film implant coating with TiCuO can provide a potent local antibacterial environment while remaining relatively nontoxic to a human osteoblast cell line. Further research in an animal model will be necessary to establish efficacy and safety of this technique and whether it might be useful in the design of implants. Clinical Relevance: A thin film coating with TiCuO demonstrates high antibacterial activity and low cellular cytotoxicity to human osteoblasts in vitro. Taken together, these properties represent a potential strategy for preventing periprosthetic infection if further work in animal models can confirm these results in vivo.